AMANWANA RESORT: INSPIRING NATURE CONSERVATION AND COMMUNITY EMPOWERMENT - Sunkar, Aryzana (ASEAN Journal on Hospitality and Tourism, 2014)
The triple bottom line of economy, ecology and socio-cultural benefits is the means to sustainable tourism, suggesting that the success of a tourism company is not only defined by the monetary gains but also by the impacts that the company's activities have on environment and society as a whole. Recognizing the sustainability of its operation rests on its ability to work harmoniously in its environmental and social settings, the Amanwana Resort management has particularly focus on direct and indirect contributions to natural environment conservation and community empowerment. As an ecotourism-based resort located in Moyo Island where the greater terrestrial part is a Hunting Park and the surrounding body of water is a Marine Recreational Park which formed the major tourism attractions, Amanwana’s planning and development of the attractions were concentrated on the need to co-exist with the fragile naturalenvironment. Amanwana’s pro-environment commitment was demonstrated byminimum alteration of local surroundings, environmental-friendly structures, the Moyo Conservation Fund to preserve forest and coral reefs habitats, nature trail walks, and employment of local villagers to protect nature from illegal logging, illegal fishing and destruction. The company’s pro-social commitment was indicated by the facilities and infrastructural development in the nearby village and local employment. As much as 85-95% of the total 120 Amanwana staffs were Indonesian, and of these 35% were locals. Residents also enjoyed the additional economic benefits of tourists staying at Amanwana Resort. Almost 20 years after its establishment, no natural disasters, ecological disturbance and social conflicts related to Amanwana Resort have been recorded.